2020
DOI: 10.7554/elife.51440
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inactivation of mTORC1 or mTORC2 in neurons reveals distinct functions in glutamatergic synaptic transmission

Abstract: Although mTOR signaling is known as a broad regulator of cell growth and proliferation, in neurons it regulates synaptic transmission, which is thought to be a major mechanism through which altered mTOR signaling leads to neurological disease. Although previous studies have delineated postsynaptic roles for mTOR, whether it regulates presynaptic function is largely unknown. Moreover, the mTOR kinase operates in two complexes, mTORC1 and mTORC2, suggesting that mTOR’s role in synaptic transmission may be comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 80 publications
10
49
1
Order By: Relevance
“…35,65 Indeed, the distinct functions of mTORC1 and mTORC2 in the postsynaptic and presynaptic sites, respectively, have been reported. 66 To conclude, our results indicate age-specific responses to IF and RAPA treatment. Both IF and RAPA altered glucose levels similarly in young and old animals.…”
Section: Figsupporting
confidence: 51%
“…35,65 Indeed, the distinct functions of mTORC1 and mTORC2 in the postsynaptic and presynaptic sites, respectively, have been reported. 66 To conclude, our results indicate age-specific responses to IF and RAPA treatment. Both IF and RAPA altered glucose levels similarly in young and old animals.…”
Section: Figsupporting
confidence: 51%
“…However, the precise role of mTORC2 is yet to be elucidated. Several studies revealed that mTORC2 may be involved in myelination of oligodendrocyte [ 48 ] and glutamate synaptic transmission [ 49 ]. Prolonged, but not acute, treatment with rapamycin was reported to lead to interference with mTORC2 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not pursue the entire interactome here, future studies investigating the interactions with members of the mTOR pathway and anaphase-promoting complex should be very fruitful. As we were preparing this work, a new study demonstrated that mTORC1 is involved in postsynaptic responses in hippocampal glutamatergic neurons, whereas mTORC2 modulates presynaptic release (McCabe et al, 2020). Given the importance of proteostasis at the synapse-and its failure in many neurological diseases (Zoghbi and Bear, 2012)-the close coordination of different protein-regulating activities is intuitively appealing.…”
Section: Implications Of the Interactomementioning
confidence: 99%